Preservative Activity of Ethanolic Extract of Ginger in Wara - A West African Traditional Soft (Unripened) Cheese - Ayanniran, Adesokan Isaac (Journal of Food Technology Research, 2014)
The effect of ethanolic extract of ginger (Zingiber officinale) on sensory and storage qualities of wara was evaluated. Pasteurized fresh milk samples were used to prepare wara and; 1.6%, 2.4%, 3.2% and 0% ginger extracts (samples A, B, C and D respectively) were incorporated into the samples separately. The wara samples were then fried in hot palm oil as it is done traditionally and organoleptic properties of the samples were determined by a taste panelist. Also physico-chemical and microbiological changes during six (6) days storage at ambient tropical temperature (30 ± 2oC) were determined. The samples (A, B and C) containing ginger were rated better than the control sample (D). Sample C had the highest overall acceptability of 4.0 while sample D had the least (2.8). During storage a significant decrease (P≤0.05) in pH with a corresponding increase in titratable acidity (TA) was recorded for the wara samples. The pH ranged between 4.17 and 6.55 while the TA ranged between 0.018 and 0.099 (mg/100g).The peroxide values (POV) of sample D increased at a faster rate than samples A, B and C. The POV for sample D after 3 days of storage was 34.15 meq/kg while that of sample C was 25.33 meq/kg at the end of 6 days storage. Although there was general increase in the microbial loads (MLs) of all the samples, the MLs of samples A, B and C were significantly lower than that of sample D. Moreover samples A and B got spoilt by day 4 of storage; sample D by day 3 while sample C was still in good condition at the end of 6 days storage. This study therefore showed that incorporation of 3.2% ethanolic ginger extract significantly improved acceptability of wara and increased the shelf life of the product by 3 days.